Local Wisdom Enriching Complementary Feeding Practices during Disaster Situations in Indonesia - Astuti, Astuti; Hayati, Happy; Waluyanti, Fajar Tri; Wanda, Dessie (Kesmas, 2022)
This study aimed to analyze complementary food fulfillment during disaster situations in Indonesia since it frequently experiences natural disasters and young children face unique challenges related to their feeding needs in disaster situations. This qualitative case study based on the Mount Merapi eruption and Sumedang landslide in 2021 collected data using observations, forum group discussions, and in-depth interviews; then, a thematic analysis was conducted. This study involved 17 participants, including Non-governmental Organizations (NGO) activists, health workers, residents involved in making complementary foods, and primary caregivers of children aged 6–24 months. This study found that there were five themes generated from the data analysis; 1) the donation of home-based complementary foods based on local wisdom, 2) inadequate complementary feeding, 3) limited resources to manage the complementary feeding, 4) clean versus dirty conditions, and 5) mothers’ endeavour in complementary feeding practices. This study concluded that the complementary feeding practices during a disaster in Indonesia were supported by NGOs, residents, and nearby healthcare workers and thus represent a form of mutual cooperation among the Indonesian people.